Karakteristik Tanah Sebagai Media Komunikasi Masyarakat Hindu Dalam Membangun Rumah Tinggal Di Kota Mataram - Ni Putu Titin Suartini; Ni Putu Sudewi Budhawati; I Nyoman Budhita (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2019)
The Hindu community in the city of Mataram considers the characteristics of land in building houses that refer to Astha Bumi, Asta Kosalakosali or other literature as the development of Balinese architecture. This study aims to reveal the reasons for choosing a residential location, the form of communication and the benefits obtained based on the characteristics of the land location of the house in the Hindu community in the city of Mataram. This research is a qualitative paradigm research with a phenomenological approach. The theoretical basis used in dissecting findings at the research site is Charles Sanders Peirce's Semiotics Theory, Paul Ricoeur's Hermeneutics Theory and Herbert Mead's Symbolic Interactionism Theory. Data collection techniques through observation, interviews and documentation. The location of the study focused on housing perumnas / BTN which was built since 1980. Informants were determined through a purposive technique with the provisions of being a Hindu who is a migrant from Bali. The results of the study showed that the Indu people chose the location of the residence based on the characteristics of the land because of the nature of the land and the location of the land. The forms of communication were personal communication and ritual or transcendent communication. Transcendent communication is carried out with ceremonies of memuhuh, melaspas, mecaru and pangupahayu, the coral reefs as a cadre of wood for poor soil characteristics. The benefits derived from the ownership of the location of Hindu homes in the city of Mataram are economically, healthly, socially, spiritually and culturally in the community so that the achievement of Tri Hita Karan is towards a sustainable, harmonious and happy balance.